Effects of Four Weeks of Strength Training on the Corticomotoneuronal Pathway - Nuzzo, James L; Barry, Benjamin K; Jones, Matthew D; Gandevia, Simon C; Taylor, Janet L (Medicine and science in sports and exercise, 2017)
Neural adaptations to strength training have long been recognized, but knowledge of mechanisms remains incomplete. Using novel techniques and a design which limited experimental bias, this study examined if 4 wk of strength training alters voluntary activation and corticospinal transmission. Twenty-one subjects were randomized into strength training (n = 10; 7 females, 3 males; 23.5 ± 7.5 yr; mean ± SD) and control groups (n = 11; 2 females, 9 males; 23.0 ± 4.2 yr). Strength training involved 12 sessions of high-force isometric contractions of the elbow flexors. Before and after training, voluntary activation of the elbow flexors was assessed via transcranial magnetic stimulation. Also, for the first time, magnetic stimulation of corticospinal axons was used to examine spinal-level adaptations to training. The evoked responses, termed cervicomedullary motor-evoked potentials (CMEPs), were acquired in resting biceps brachii in three arm postures. Muscle adaptations were assessed via electrical stimulation of biceps. Compared with the control group, the strength training group exhibited greater increases in maximal strength (12.8% ± 6.8% vs 0.0% ± 2.7%; P < 0.001), biceps electromyographic activity (27.8% ± 25.9% vs -5.2% ± 16.8%; P = 0.002), and voluntary activation (4.7% ± 3.9% raw change vs -0.1% ± 5.2%; P = 0.034). Biceps CMEPs in all arm postures were unchanged after training. Biceps twitch characteristics were also unchanged. Four weeks of isometric strength training of the elbow flexors increased muscle strength and voluntary activation, without a change in the muscle. The improvement in activation suggests that voluntary output from the cortex was better able to recruit motoneurons and/or increase their firing rates. The lack of change in CMEPs indicates that neither corticospinal transmission nor motoneuron excitability was affected by training.